MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI MULTIMEDIA PEMBELAJARAN INTERAKTIF ARTIKULATE STORYLINE PADA MATERI TEOREMA PYTHAGORAS KELAS VIII SMP N 3 KWANDANG - Kulupani, Hasmiati H (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to evaluate whether the use of interactive learning multimedia Artiulate Storyline can improve mathematics learning outcomes in the Pythagorean Theorem material. This study was conducted at SMP Negeri 3 Kwandang in the 2024-2025 academic year. This study is a Classroom Action Research (CAR) which was carried out in only 1 cycle. The subjects in the study were 25 grade VIII students. Data collection techniques involved observation and testing, with research instruments in the form of teacher observation sheets, student activity observation sheets and essay test questions. The results of the study showed that the results of teacher observations for the category were at least good or very good with a percentage and in student activities, the observation criteria were divided into 4 aspects of observation with an average percentage, namely (1) student readiness in receiving material 91%, (2) student participation in learning 89%, (3) student cooperation in learning 91%, and (4) student activities in closing learning 92%. Meanwhile, for the learning outcomes of students who obtained scores reaching the Minimum Completion Criteria (KKM) with completion of 23 students with a percentage of 88% and incomplete around 3 students with a percentage of 12%. The average mathematics learning outcomes of students on the Pythagorean theorem material meet the success indicators.